Epidemiological profile of tuberculosis in the northeast of Brazil: temporary series from 2008 to 2018 (Research, Society and Development, 2020)
To evaluate the tuberculosis incidence in the Northeast Region of Brazil, in the period of 2008-2018. Quantitative, descriptive and retrospective epidemiological study, conducted from the analysis, in the database of the Information System of Diseases and Notices of the Unified Health System, of notified cases of tuberculosis in the Northeast Region of Brazil between the years 2008 and 2018. In the Northeast, there was a reduction in its incidence in recent years; the male gender had a higher number of cases. The most affected age groups were young adults. Both socioeconomic and intrinsic factors are major contributors to the maintenance of tuberculosis rates in the Northeast of the country. Tuberculosis tended to reduce its incidence; however, it still represents a major problem in northeastern Brazil. Attention is needed to the states of Pernambuco and Ceará.